Solar Assisted Dryer for Municipal Solid Waste - Pravin D.Pawale; Sumit S.Dharmarao; Prof. Dr. Maruti S.Pawar (International Journal of Innovations in Engineering Research and Technology, 2021)
Urban India generates 188,500 tons per day (68.8 million tons per year)of municipal solid waste (MSW) at aper capita waste generation rate of 500 grams/person/day.Improper solid waste management deterioratespublic health, degrades quality of life, and pollutes local air,water and land resources. It also causes globalwarming and climate change and impacts the entire planet. Improper waste management is also identified asa cause of 22 human diseases and results in numerous premature deaths every year.The composition ofurban MSW in India is 51% organics, 17.5% recyclables (paper, plastic, metal, and glass) and 31 % of inerts.The moisture content of urban MSW is 47% and the average calorificvalue is 7.3 MJ/kg (1745 kcal/kg). Thecomposition of MSW in the North, East, South and Western regions of thecountry varied between 50-57%of organics, 16-19% of recyclables, 28-31% of inerts and 45-51% of moisture. The calorific value of thewaste varied between 6.8-9.8 MJ/kg (1,620-2,340 kcal/kg).Currently,there is no system or mechanism existsto dry the municipal solid waste. In this research work such system can be designed and developed whichwill dry the municipal solid waste and remove the odor from it.Dried municipal solid waste can be furtherused as fuel for boiler.